Better or Worse: a Study of Day-to-Day Changes over Five Months of Rosen Method Bodywork Treatment for Chronic Low Back Pain - Fogel, PhD, LMT, Certified Rosen Method Bodywork Teacher and Practitioner, Alan (International Journal of Therapeutic Massage & Bodywork, 2013)
Background: Fluctuations of good days and bad days—in physical symptoms and emotional states—are common for individuals with chronic illness. This pilot study examines these fluctuations during bodywork treatment.Purpose: We analyzed changes in daily selfreports over a period of five months for five individuals who received weekly treatments of Rosen Method Bodywork (RMB), which uses touch and words to enhance body awareness of physical sensations and emotional states.Subjects and Design: Five subjects (aged 31–56) who had chronic low back pain (CLBP) received 16 weekly treatments given by three experienced RMB practitioners.Measures: Pre- and posttreatment assessments covered demographics, disability, and pain. Clients also completed daily bedtime assessments of pain, fatigue, emotional state, and sense of control during the entire treatment period.Results: All clients reported reductions in pain and/or disability in post- compared to pretreatment. In spite of a high level of day-to-day variability in the daily assessments, there were significant reductions in pain and fatigue, and significant increases in positive emotional state and sense of control across the treatment period. In reaching this end, however, some clients had slow and steady improvements, some improved more rapidly, while others got worse before they got better.Conclusions: The natural course of healing— with its inevitable fluctuations in symptoms—is part of a process leading to successful treatment outcomes. Rosen Method Bodywork may be especially helpful in developing and accepting both sensory and emotional body awareness changes that facilitate overall improvement.